Organophosphorus pesticide residues detected in eggplant and tomato samples collected from different regions of Bangladesh - Ahmed, Md Sultan; Begum, Afroza; Hossain Prodhan, Mohammad Dalower; Afroze, Marina; Sarker, Debasish (Asian-Australasian Journal of Food Safety and Security, 2021)
The study was conducted to detect and quantify the residue of seven commonly used organophosphorus pesticides (acephate, chlorpyrifos, quinalphos, diazinon, malathion, dimethoate and fenitrothion) in eggplant and tomato samples collected from local market of commercially grown four different regions viz. Bogura, Narsingdi, Jeshore and Cumilla for the comparison between the detected residue level with maximum residue limit (MRL) set by European Union. A total of 80 analyzed samples of eggplant and tomato, 21.25% of the total number of samples contaminated with acephate, chlorpyrifos, fenitrothion and diazinon residues which were above the EU-MRLs. Out of 40 analyzed samples of eggplant, 11 samples were contaminated with acephate, diazinon fenitrothion and chlorpyrifos residues. All of the contaminated samples (27.5% of the total number of samples) had chlorpyrifos (0.02-0.046), acephate (0.017-0-0.39), diazinon (0.11-0.47) and fenitrothion (0.20) residues which were above the EU-MRLs. The eggplant samples collected from Jeshore and Narsingdi received more pesticides than Cumilla and Bogura regions. In case of 40 analyzed samples of tomato, 6 samples (15% of the total number of samples) had chlorpyrifos (0.27-0.43), diazinon (0.25) and fenitrothion (0.10) residues which were above EU-MRLs. Malathion, quinalphos and dimethoate residues were not found in any of the tested samples which might be applied at recommended doses. Asian Australas. J. Food Saf. Secur. 2021, 5 (1), 27-31